ANALISIS PERAN SUBSEKTOR PERTANIAN TERHADAP PEMBANGUNAN KABUPATEN KARANGANYAR; SEBUAH PENDEKATAN COMPARATIVE PERFORMANCE INDEX - Fransisca Erna S.; Mohamad Harisudin; Wiwit Rahayu (Universitas Sebelas Maret, 2017)
Abstract: The objective of this study was to determine how much of the total share, rateof contribution and rate of growth of agriculture sector on regional development inKaranganyar; determine the classification of agriculture sector in Karanganyar usingKlassen typology; and knowing the agriculture sector featured in Karanganyarregency. The research location was Karanganyar Regency. The data used in this studyis primary data and secondary data. Data analysis methods used were: (1)Analysis ofthe magnitude of the total share of agricultural subsectors using shift share analysis;(2)Identification of the contribution and the growth rate of agriculture subsector;(3)The classification of agriculture subsector in Karanganyar using Klassen typology;and (4)Identification of featured subsector agricultural sector in Karanganyar usingComparative Performance Index (CPI). The results showed: total share of food crops,plantation subsector, livestock susbector, forestry subsector, and the fisheriessubsector respectively 173.644,66 million rupiah; 24.928,24 million rupiah; 56.674,21million rupiah; 829,48 million rupiah; and 1.153,37 million rupiah. Contribution ofthe food-stuff crops subsector, plantation subsector, animal husbandry subsector,forestry subsector, and fisheries subsector respectively by 66.94%; 8.71%; 23.36%;0.48%; and 0.52%. The growth rate of the food-stuff crops subsector, plantationsubsector, animal husbandry subsector, forestry subsector, and fisheries subsectorrespectively by 6.29%; 6.70%; 5.41%; 3.92%; and 5.16%. Karanganyar animalhusbandry subsector is developed and emerging subsector. Food-stuff crops subsector,plantation subsector, forestry subsector, and fisheries subsector were classified ingrowing subsectors but depressed. The first featured the agricultural subsector basedon analysis of the CPI was the food crops subsector.Abstrak: Penelitian ini bertujuan untuk (1) mengetahui besar total share, kontribusi,dan laju pertumbuhan subsektor pertanian terhadap pembangunan KabupatenKaranganyar, (2) mengklasifikasikan subsektor pertanian di Kabupaten Karanganyarmenggunakan tipologi klassen, dan (3) mengetahui subsektor pertanian unggulanKabupaten Karanganyar. Lokasi penelitian dipilih secara sengaja (purposive) yaituKabupaten Karanganyar. Data yang digunakan adalah data primer dan data sekunder.Analisis data yang digunakan adalah analisis shift share, analisis kontribusi dan lajupertumbuhan, analisis tipologi klassen, dan analisis comparative performance index.Hasil penelitian menunjukkan total share subsektor tanaman bahan makanan,subsektor perkebunan, subsektor peternakan, subsektor kehutanan, dan subsektorperikanan Kabupaten Karanganyar masing-masing sebesar 173.644,66 juta rupiah; 24.928,24 juta rupiah; 56.674,21 juta rupiah; 829,48 juta rupiah; dan 1.153,37 jutarupiah. Kontribusi subsektor tanaman bahan makanan, subsektor perkebunan,subsektor peternakan, subsektor kehutanan, dan subsektor perikanan masing-masingsebesar 66,94%; 8,71%; 23,36%; 0,48%; dan 0,52%. Laju pertumbuhan subsektortanaman bahan makanan, subsektor perkebunan, subsektor peternakan, subsektorkehutanan, dan subsektor perikanan masing-masing sebesar 4,88%; 5,75%; 5,27%;4,01%; dan 5,89%. Subsektor peternakan Kabupaten Karanganyar merupakansubsektor maju dan berkembang. Subsektor tanaman bahan makanan, subsektorperkebunan, subsektor kehutanan, dan subsektor perikanan diklasifikasikan dalamsubsektor berkembang tapi tertekan. Subsektor pertanian unggulan pertamaberdasarkan analisis CPI adalah subsektor tanaman bahan makanan.